Uprizarjanje literature in bralne uprizoritve - Orel, Barbara (Amfiteater (Ljubljana), 2023)
In 2005, on the initiative of playwright Simona Semenič and in close collaboration with performing arts theorist Rok Vevar, a group of playwrights and dramaturgs founded PreGlej within the Glej Theatre in Ljubljana, Slovenia. The group confronted the issues of playwriting and, within a few years, established a platform for the creation, development and international exchange of dramatic writing. Their work was committed to establishing the conditions necessary for creating dramatic texts. To this end, they used the form of staged readings – not only as a public presentation of dramatic plays but as a method for developing drama, bringing drama as a work in progress. The article shows that this kind of playwriting practice on Slovenian stages has its precursors in the experimental theatre practices of the 1960s and 1970s (as applied by the neo-avant-garde groups of poets 441/442/443, Nomenklatura and LKB – Literarni klub Branik, as well as in the performances of writers presenting their literary works at the Pekarna Theatre). Poets and writers staged their works, which were not primarily intended to be performed, creating theatrical forms of writing for the stage, which fit neither the conventions of drama nor the tradition of theatre. The staging of literature and staged readings are discussed in the context of performance writing, which characterises the multiple relationships between writing and performance, focusing on the process of writing as a performative act.
Keywords: bralna uprizoritev; drama; literatura; literature; performance; performance writing; poetry; poezija; staged reading; uprizoritev; uprizoritveno pisanje